2015
DOI: 10.1155/2015/817481
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Depression and Quality of Life in Patients of Lichen Planus

Abstract: The precise cause of lichen planus is unknown, but the disease seems to be immunologically mediated. It is a psychocutaneous disorder. Due to scarcity of Indian studies in this field, we decided to study in patients of lichen planus the prevalence of depression and quality of life with comparison of the same in both the genders. Patients diagnosed as having lichen planus by consultant dermatologist were enrolled after informed consent and ethics approval. 45 patients were screened, of which 35 who satisfied th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 24 publications
6
38
0
1
Order By: Relevance
“…Studies by Pekiner FN et al 17 , who stated that higher 21 also found higher anxiety and depression levels in OLP patients but using different psychometric tests which were in accordance with present study which proves strong association of OLP with stress, anxiety and depression levels.…”
Section: Discussion:-supporting
confidence: 91%
“…Studies by Pekiner FN et al 17 , who stated that higher 21 also found higher anxiety and depression levels in OLP patients but using different psychometric tests which were in accordance with present study which proves strong association of OLP with stress, anxiety and depression levels.…”
Section: Discussion:-supporting
confidence: 91%
“…Some authors didn't demonstrate this connection [23], however others confirmed that disorders connected with depression more often includes women (77,7 %, 7 from 9 people, who are affected with lichen planus with depression are women) [22]. The cause of it is that women have higher vulnerability to stress, more often they are not satisfied with their appearance, and lower self-esteem than men [22]. These differences between sexes were observed in the school and work, not in other environments [22].…”
Section: Connection With Mental Diseasesmentioning
confidence: 98%
“…There is the connection between mental state and prevalence of dermatological illnesses. From one point of view psychiatric disorders can have impact on exacerbation or acceleration of dermatological disease, and in other hand disorders, which are connected with the skin can be the reason of psychiatric illnesses [22]. Because of this and lack of well-known knowledge about etiopathogenesis of LP, it is consider to be psychosomatic illness [23].…”
Section: Connection With Mental Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our skin is a reflection of our health, and numerous diseases caused by organic or psychological factors may manifest as either pathologically altered structures of the skin or as subjective symptoms with normal skin. Lichen planus (LP) was recently reported to be a psychocutaneous disorder that affects skin, mucosa, hair follicles, and nails (Sawant et al, 2015). The most common psychogenic conditions that may lead to LP are depression, anxiety, and stress (Pokupec, Gruden, & Gruden, 2009).…”
Section: Dear Editormentioning
confidence: 99%